Complete secondary choral music guide - Roach, Donald W. (West Nyack, N.Y. : Parker, 1989)
This book is divided into four parts: Administration of Junior and Senior High School Choruses; The Conductor and the Choral Score; Developing Choral Musicianship in Students; and Planning Rehearsals and Performances.
Keywords: Choral singing; Choral conducting; Choirs; Choirs (Music); Choral singing -- Instruction and study -- Juvenile; Choral conducting